View of the city of Vienna the capital of Germany - Chesham, Francis, 1749-1806 (engraver):::Creator::::::::::::; Middleton, Charles, 1756-ca. 1818 (author):::Contributor:::::::::::: (United Kingdom; London?)
Engraving with a panoramic view of Vienna from across the Danube, with peasants in the foreground.